THE PROBLEM OF STUDENT KNOWLEDGE CONTROL AND ACCOUNTING IN THE PRACTICE OF UKRAINIAN NEVER 20s PP. XX CENTURY - H.P. Polishchuk (Освітній вимір, 2003)
The article deals with the methods of control and registration of pupils’ knowledge in the twenties of the last century.